Biocidal activity of curcumin and cationic polymer possessing composites - Eren, Tarik; Baysal, Gulay; Dogan, Faik (SAGE PUBLICATIONS LTD, 2020)
There is a growing interest in new type of biocidal compounds with antibacterial properties against bacteria. In this study, new antibacterial synthetic materials bearing curcumin and cationic polymers were synthesized. In the synthesis stage, the methacrylate functional cationic monomer was synthesized via the Michael addition route by using 3-acryloxy-2-hydroxypropyl methacrylate and 3-amino pyridine to obtain Monomer 1. Monomer 1 was further quaternized with hexyl bromide to obtain a cationic methacrylate functional monomer. Free-radical polymerization of Monomer 1 and methyl acrylate was conducted in the presence of azobisisobutyronitrile under dimethylformamide solvent. The composite formulation was conducted by using turmeric extractCurcuma longa(curcumin), hydroxyapatite, montmorillonite, and silver nitrate. The materials were analyzed by using the methods of X-ray diffraction, nuclear magnetic resonance, Fourier transform infrared spectroscopy, and scanning electron microscopy. The biocidal activities against the bacteriaEscherichia coli, Listeria monocytogenes, Salmonella, andStaphylococcus aureuswere analyzed using agar well diffusion method. From the Fourier transform infrared, X-ray diffraction, and scanning electron microscopy analysis results of the synthesized nanocomposites, it is seen that they form strong connections with the components added to the composites and form an exfoliated structure. According to the antibacterial analysis results, the nanocomposites obtained have showed a strong antibacterial resistance againstE.coli, L.monocytogenes, Salmonella, andS. aureusbacteria, and the high inhibition zone areas were obtained.
Keywords: Cationic polymers; curcumin; biocidal activity; nanocomposites; PMMA; PRODUCTS; FILMS; Biotechnology & Applied Microbiology; Materials Science; Polymer Science